Beneficial effects associated to a healthy lifestyle in systemic lupus erythematosus: A cross-sectional study. (June 2023) - Vordenbäumen, Stefan; Kleefisch, Martin; Sokolowski, Alexander; Düsing, Christina; Richter, Jutta G; Brinks, Ralph; Schneider, Matthias; Chehab, Gamal
Objective: To assess whether a healthy lifestyle is associated to beneficial effects on various systemic lupus erythematosus (SLE) health domains. Methods: In a cross-sectional study, Mediterranean Diet Adherence Score (MEDAS), physical activity energy expenditure (PAEE), and smoking status were assessed by questionnaires, along with clinical parameters and various health domains including Systemic Lupus Disease Activity Score (SLEDAI), Depression Scale (CES-D), Fatigue Severity (FSS), functional status (FFbH), physical and mental quality of life (PCS, MCS). Lifestyle choices were assessed with respect to health domains by linear regression modeling. Additionally, SLE patients with a healthy lifestyle (MEDAS ≥ 4, ≥ 1 h sport per week, no smoking) were compared to those without by Wilcoxon's signed-rank test. Results: 49 of 145 SLE patients (44.3 ± 31.7 years, 87.6% female) followed a healthy lifestyle and showed a higher physical quality of life (β = 4.5 (95%-CI 1.5–7.9) p = 0.01), lower depression (β = −5.0 (−8.2 to −0.2) p = 0.02) and lower fatigue (β = −0.8 (−1.5 to −0.2) p = 0.01) independently of SLE disease activity. Furthermore, dsDNA-antibodies were lower (146 ± 540 vs 266 ± 146 U/mL, p = 0.049). In a more detailed analysis, physical activity had the highest impact on the various health domains when compared to smoking or diet adherence, which was consistent even after adjusting for multiple potential confounders. Each 1, 000 kcal of weekly PAEE was associated to a 1.8 (0.9–2.6) point increase in the PCS ( p = 0.0001), a 0.2 (0.03–0.4) point decrease in the CES-D ( p = 0.01) and a 2.8 (1.2–4.4) point increase in the FFbH ( p = 0.0006). Conclusion: A healthy lifestyle, especially physical activity is associated with beneficial effects including quality of life, depression and fatigue in SLE.